Combining Ability and Molecular Genetic Distances in Tropical Maize Lines for Grain Yield and Agronomic Traits. Issue 3 (27th May 2017) - Gichuru, Lilian; Derera, John; Tongoona, Pangirayi; Murenga, Mwimali
Abstract : Ascertaining the relationship of genetic diversity and combining ability would aid the design of a breeding strategy for maize hybrids. Twelve tropical maize inbreds were crossed in a half-diallel to study gene action for yield and other traits and also to determine the relationship between heterosis, combining ability for grain yield and molecular genetic distance in the set of lines. Sixty-six crosses and their 12 parental lines were evaluated in five Kenyan locations in 2011 and 2012. Genetic distances between lines was quantified using 28 SSR markers. General combining ability (GCA) and specific combining ability (SCA) mean squares were both important for grain yield and other traits. However, SCA was more important than GCA for grain yield. Line C92 had the best GCA effects (0.63; p < 0.001), whereas MUL71 × OSU23i (1.11; p < 0.01) had the highest SCA. The correlation coefficient between genetic distance (GD) and SCA was high, positive and significant (0.62; p < 0.001), as was that between GD and heterosis (0.68; p < 0.001), suggesting some predictive value. Cluster analysis based on simple sequence repeat (SSR) markers revealed three groups that were in conformity with SCA and heterosis clusters. This study supports the use of the selected SSR markers for further exploration as a complementary tool to field evaluations for heterotic grouping.